Gelatinase contributes to the pathogenesis of endocarditis caused by Enterococcus faecalis - Thurlow, Lance R.; Thomas, Vinai Chittezham; Narayan, Sanjeev K.; Olson, Sally A.; Fleming, Sherry D.; Hancock, Lynn E. (My University, 2013)
The Gram-positive pathogen Enterococcus faecalis is a leading agent of nosocomial infections including urinary tract infections, surgical site infections, and bacteremia. Among the infections caused by E. faecalis, endocarditis remains a serious clinical manifestation and unique in that it is commonly acquired in a community setting. Infective endocarditis is a complex disease with many host and microbial components contributing to the formation of bacterial biofilm-like vegetations on the aortic valve and adjacent areas within the heart. In the current study, we compared the pathogenic potential of the vancomycin resistant E. faecalis V583 and three isogenic protease mutants (ΔgelE, ΔsprE and ΔgelEsprE) in a rabbit model of enterococcal endocarditis. The bacterial burdens displayed by GelEˉ mutants (ΔgelE , ΔgelEsprE) in the heart were significantly lower compared to V583 or the SprEˉ mutant. Vegetations on the aortic valve infected with GelEˉ mutants (ΔgelE; ΔgelEsprE) also showed a significant increase in deposition of fibrinous matrix layer and increased chemotaxis of inflammatory cells. In support of a role for proteolytic modulation of the immune response to E. faecalis, we also demonstrate that GelE can cleave the anaphylatoxin complement C5a and that this proteolysis leads to decreased neutrophil migration in vitro. In vivo, a decreased heterophil (neutrophil-like cells) migration was observed at tissue sites infected with GelE producing strains, but not by SprE producing strains. Taken together, these observations suggest that of the two enterococcal proteases, gelatinase is the principal mediator of pathogenesis in endocarditis.
Keywords: Enterococcus faecalis; Gelatinase; Endocarditis